All Wrapped Up in Ethocel - Dow Chemical Company (1938)
Color print advertisement for Ethocel, the brand name for Dow Ethylcellulose, marketed for its flexibility and shock resistance under extreme high and low temperatures. The advertisement features an illustration of the Earth, depicted as a globe encased in a clear plastic wrapper. The accompanying text describes the many applications of Ethocel for industrial and commercial use, particularly as a packaging material.
Keywords: Advertising; Dow Chemical Company; Chemical industry; Corporations; Plastics; Plastics industry and trade; Ethylcellulose; Plastics in packaging